Market Structure, Competition, and Pricing in United States International Telephone Service Markets - Madden, Gary; Savage, Scott J. (The Review of Economics and Statistics, 2000)
Several national governments argue international telephone prices are high because of asymmetric competition and inefficiencies in the accounting arrangements that govern the telecommunications services trade. This paper develops a model of U.S. international telephone pricing that allows for the accounting rate system and contains market-structure variables for both the U.S. and foreign ends of bilateral markets. Model estimation is on 39 bilateral telephone markets from 1991 through 1994. Parameter estimates reveal that settlement rates, market concentration, competition at either end of the bilateral market, and ownership are significant determinants of prices. These findings support initiatives promoting accounting-rate reductions and increased competition.